Empirical Evidence on Audit Quality under a Dual Mandatory Auditor Rotation Rule. Issue 1 (1st January 2021) - Horton, Joanne; Livne, Gilad; Pettinicchio, Angela
Abstract: Regulators in the US ruled against introducing mandatory firm rotations in addition to the existing rule for periodic partner rotations. In contrast, European regulators ruled in favor of a dual mandatory rotation rule in which both audit firm and audit partner rotations are required. Employing a unique setting where a dual regime of audit and firm rotations are required, we assess the net benefit (cost), of audit firm rotation incrementally to partner rotation. Specifically, we analyze several earnings-based measures of audit quality along with the market perception of audit quality. Controlling for partner rotation, we do not find that firm rotations have a positive incremental effect. In contrast, we find audit partner rotation under the dual regime appears to improve both the earnings-based measures of audit quality, and market perceptions of earnings. Our evidence suggests that any benefit arising from dual rotation is likely to be driven by the change in partner. However, whether the audit firm rotation should still be required is unclear, given that the observed benefits arising from the audit partner rotation could potentially be preconditioned on audit firm rotation.